1994
DOI: 10.1016/s0741-5214(94)70082-6
|View full text |Cite
|
Sign up to set email alerts
|

Stenting of proximal venous obstructions to maintain hemodialysis access

Abstract: Stenting of subclavian and innominate venous stenoses and occlusions effectively corrected the underlying lesions responsible for disturbed hemodynamics and, in most cases, prolonged available hemodialysis access from the affected side. Stents seem to be valuable adjuncts in the management of failing hemodialysis access due to central venous stenosis or occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 10 publications
1
34
0
1
Order By: Relevance
“…83,84,98,100 Results of these procedures in the subclavian and internal jugular veins are satisfactory, but subclavian stents may be complicated by the scissoring effects of the first rib and the clavicle, resulting in permanent deformation. A summary of these interventions over the past decade reported a 12-month patency ranging from 11% to 68% for central venous stents and 11% to 35% for PTA alone.…”
Section: Central Venous Stenosis or Occlusionmentioning
confidence: 99%
“…83,84,98,100 Results of these procedures in the subclavian and internal jugular veins are satisfactory, but subclavian stents may be complicated by the scissoring effects of the first rib and the clavicle, resulting in permanent deformation. A summary of these interventions over the past decade reported a 12-month patency ranging from 11% to 68% for central venous stents and 11% to 35% for PTA alone.…”
Section: Central Venous Stenosis or Occlusionmentioning
confidence: 99%
“…Some groups routinely perform stent placement for central venous stenosis; they have reported improved patency rates compared to those with PTA alone. 8,9) On the contrary, other groups reported that the primary patencies between angioplasty and stent were not significantly different. 10,11) Further, Ozyer et al 12) reported that stent placement for central venous stenosis or occlusion led to a significantly lower primary patency rate than PTA but added to the longevity of vein patency in angioplasty-resistant lesions; therefore, stent placement should be considered in such angioplasty-resistant lesions.…”
Section: Discussionmentioning
confidence: 93%
“…Endovascular treatment for central venous stenosis or occlusion is well-known as a safe and effective procedure in HD patients. [8][9][10][11][12] However, the optimal choice between PTA and stent placement in the management of central venous stenosis and occlusion still remains controversial. Some groups routinely perform stent placement for central venous stenosis; they have reported improved patency rates compared to those with PTA alone.…”
Section: Discussionmentioning
confidence: 99%
“…Venous hypertension due to stenosis or thrombosis distal to the AVF can usually be treated by the use of endovascular techniques 30,31 (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%